Road Asset Governance Filter : Case Study of Kazakhstan and Armenia - Queiroz, Cesar (World Bank, Washington, DC, 2014)
Building upon the transport governance filter developed by the Europe and Central Asia (ECA) transport team, which identified several thematic principles and actionable indicators on the governance of the transport sector at large, this paper seeks to assess the overall governance performance of the road sector as well as the concrete issues that road administrations should address in order to improve sector governance. A pilot survey was conducted in Armenia and Kazakhstan, in which road sector stakeholders were asked to evaluate more than seventy questions structured along four governance dimensions: (i) transparency, disclosure and accountability of the road agency; (ii) transparent and accessible procurement processes; (iii) financial management system; and (iv) administrative procedures and anticorruption effort. This report starts with an overview of the existing approaches to governance and corruption with a particular focus on the road sector. It then outlines the methodological framework developed under the study to assess the governance challenges facing the road sector, and report the governance challenges in Armenia and Kazakhstan using the methodology developed. The report will conclude with an assessment of the strengths and weaknesses of the methodological approach used and concrete suggestions to strengthen governance in the road sector of Armenia and Kazakhstan.